2013
DOI: 10.1111/hepr.12141
|View full text |Cite
|
Sign up to set email alerts
|

Serum transferrin as a predictor of prognosis for hepatic arterial infusion chemotherapy in advanced hepatocellular carcinoma

Abstract: Serum transferrin could be useful as a prognostic predictor in advanced HCC patients before HAIC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Regarding the prognostic factor of HAIC, lower AFP was associated with longer survival, and favorable hepatic reserve capacity was associated not only with survival but also better therapeutic effect after HAIC . Recently, serum vascular endothelial growth factor (VEGF) and transferrin were shown to be possible predictive factors for therapeutic effect and survival . In this study, NLR was also shown to be a candidate prognostic marker in treatment with HAIC‐mFP.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Regarding the prognostic factor of HAIC, lower AFP was associated with longer survival, and favorable hepatic reserve capacity was associated not only with survival but also better therapeutic effect after HAIC . Recently, serum vascular endothelial growth factor (VEGF) and transferrin were shown to be possible predictive factors for therapeutic effect and survival . In this study, NLR was also shown to be a candidate prognostic marker in treatment with HAIC‐mFP.…”
Section: Discussionmentioning
confidence: 53%
“…29,35 Recently, serum vascular endothelial growth factor (VEGF) and transferrin were shown to be possible predictive factors for therapeutic effect and survival. 30,36 In this study, NLR was also shown to be a candidate prognostic marker in treatment with HAIC-mFP. A recent meta-analysis indicated that NLR is a convenient, easily obtained, low cost and reliable predictor of HCC, 22 and it has been reported to be associated with early recurrence and poorer survival of HCC based on the results of studies from cohorts after hepatectomy or liver transplantation 37,38 and TACE.…”
Section: Discussionmentioning
confidence: 65%
“…Transferrin, a native chelator involved in iron homeostasis, may act as an anticancer agent in a similar manner as deferoxamine. In a study by Zaitsu et al [38], transferrin levels significantly correlated with MSTs in HCC patients undergoing HAIC (MSTs were 12.0 and 4.9 months for ≥190 mg/dL and ≤190 mg/dL transferrin, respectively). A serum transferrin level ≥190 mg/dL (hazard ratio, 0.282; 95% CI, 0.132-0.603; p=0.001) was identified as an independent prognostic indicator in a multivariate analysis, as was Child-Pugh B (hazard ratio, 1.956; 95% CI, 1.034-3.700; p=0.039).…”
Section: Predictive Factors For Response and Survivalmentioning
confidence: 95%
“…The poor prognostic predictors include not only tumor-associated factors, such as more than three tumors[ 49 ], large tumors (> 3 cm)[ 49 ], the presence of vascular invasion[ 49 , 53 ], the presence of extrahepatic metastasis[ 49 , 58 , 61 ] and high AFP levels[ 49 , 58 , 61 ], but also those associated with the patient, including dysfunction of the liver reserve[ 48 , 49 , 53 , 58 - 61 ], ECOG PS 1-2[ 58 , 61 ], and a positive HBs antigen test result[ 49 ]. Additionally, poor prognostic predictors include negative responses of AFP or DCP[ 48 ], high levels of inflammation-related markers such as NLR and CRP[ 58 ], low transferrin levels (< 190 mg/dL)[ 59 ] and high VEGF levels (≥ 100 pg/mL)[ 60 ].…”
Section: Haic For Advanced Hccmentioning
confidence: 99%